Setting priorities to avoid deforestation in Amazon protected areas: are we choosing the right indicators? - Christoph Nolte; Arun Agrawal; Paulo Barreto (Environmental Research Letters, 2013)
Cost-effective protected area networks require that decision makers have sufficient information to allocate investments in ways that generate the greatest positive impacts. With applications in more than 50 countries, the Rapid Assessment and Prioritization of Protected Area Management (RAPPAM) method is arguably the tool used most widely to assist such prioritization. The extent to which its indicators provide useful measures of a protected area’s capacity to achieve its conservation objectives, however, has seldom been subject to empirical scrutiny. We use a rich spatial dataset and time series data from 66 forest protected areas in the Brazilian Amazon to examine whether RAPPAM scores are associated with success in avoiding deforestation. We find no statistically significant association between avoided deforestation and indicators that reflect preferential targets of conservation investments, including budget, staff, equipment, management plans and stakeholder collaboration. Instead, we find that the absence of unsettled land tenure conflicts is consistently associated strongly with success in reducing deforestation pressures. Our results underscore the importance of tracking and resolving land tenure in protected area management, and lead us to call for more rigorous assessments of existing strategies for assessing and prioritizing management interventions in protected areas.